2021
DOI: 10.33221/jiiki.v11i01.951
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Factors Affecting Self-Care Activities of Patients with Hypertension

Abstract: Introduction: Hypertension is one of the non- communicable diseases that causes the highest mortality. Self-care activities are factors that determine the health status and quality of life of people with hypertension. Objectives: The aim of the study was to determine the direct and indirect effects and the magnitude of the variables of the role of health workers, family functions, health literacy, and self-efficacy on self-care activities for hypertension sufferers at the Tanah Sareal Health Center, Bogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Self-care is a form of self-reliance in maintaining health (Istiani & Rokhmiati, 2021). The study entitled "Self-Management Intervention Of Elderly Hypertension: A Literature Review" revealed that self-care management in hypertension consists of medication adherence, health monitoring, diet management, exercise management, work management, and emotional management.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…Self-care is a form of self-reliance in maintaining health (Istiani & Rokhmiati, 2021). The study entitled "Self-Management Intervention Of Elderly Hypertension: A Literature Review" revealed that self-care management in hypertension consists of medication adherence, health monitoring, diet management, exercise management, work management, and emotional management.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%